(untitled) (Muitas Vozes, 2021)
This article aimed to analyze Clarice Lispector’s single theatrical work, the play “The burnt sinner and the harmonious angels”. The main focus lied on the analysis of the main character’s smile as the sole mean of expression in the whole act, as a manifestation of resistance against the establishment that organizes her death. The conclusion reached in the analysis of the sinner’s smile reveals itself to be Clarice’s small war machine which subverts and changes the expectation not only for punishment but also for the restoration of the social order expected by the condemnatory act. This manifestation was considered a guerilla act, silent and inventive, which mobilizes against the state establishment. For such analysis, Deleuze and Guattari’s thinking in A Thousand Plateaus, especially in plateau 12,227 – Nomadology: The War Machine, was employed, as well as some concepts from the Theatre of Cruelty of Antonin Artaud.